Quantitative textural measurements in igneous and metamorphic petrology - Higgins, Michael Denis, 1952- (Cambridge University Press, 2006)
Recent advances in the quantification of crystalline rock textures have allowed textural measurements to compete with and complement the chemical and isotopic studies. This book discusses aspects of petrological theory and presents typical applications of textural studies. It will be of great interest to all researchers and graduate students in petrology.